Substitution-inert trinuclear platinum complexes efficiently condense/aggregate nucleic acids and inhibit enzymatic activity - Malina, Jaroslav; Farrell, Nicholas P; Brabec, Viktor (Angewandte Chemie (International ed. in English), 2014)
The trinuclear platinum complexes (TriplatinNC-A [{Pt(NH3 )3 }2 -μ-{trans-Pt(NH3 )2 (NH2 (CH2 )6 NH2 )2 }](6+) , and TriplatinNC [{trans-Pt(NH3 )2 (NH2 (CH2 )6 NH3 (+) )}2 -μ-{trans-Pt(NH3 )2 (NH2 (CH2 )6 NH2 )2 }](8+) ) are biologically active agents that bind to DNA through noncovalent (hydrogen bonding, electrostatic) interactions. Herein, we show that TriplatinNC condenses DNA with a much higher potency than conventional DNA condensing agents. Both complexes induce aggregation of small transfer RNA molecules, and TriplatinNC in particular completely inhibits DNA transcription at lower concentrations than naturally occurring spermine. Topoisomerase I-mediated relaxation of supercoiled DNA was inhibited by TriplatinNC-A and TriplatinNC at concentrations which were 60 times and 250 times lower than that of spermine. The mechanisms for the biological activity of TriplatinNC-A and TriplatinNC may be associated with their ability to condense/aggregate nucleic acids with consequent inhibitory effects on crucial enzymatic activities.
Keywords: Molecular Structure; Organoplatinum Compounds; DNA; organoplatinové sloučeniny; inhibitory topoisomerasy I; Topoisomerase I Inhibitors; tRNA; DNA-topoisomerasy I; DNA Topoisomerases, Type I; Plasmids; DNA condensation; plazmidy; platinum; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; topoisomerase I; nucleic acids; molekulární struktura